2010
DOI: 10.1038/onc.2010.196
|View full text |Cite|
|
Sign up to set email alerts
|

Predicting the site of origin of tumors by a gene expression signature derived from normal tissues

Abstract: Multiple expression signatures for the prediction of the site of origin of metastatic cancer of unknown primary origin (CUP) have been developed. Owing to their limited coverage of tumor types and suboptimal prediction accuracy on distinct tumors, there is still room for alternative CUP gene expression signatures. Whereas in past studies, CUP classifiers were trained solely on data from tumor samples, we now use expression patterns from normal tissues for classifier training. This approach potentially avoids p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…''bulk'' molecular profiling (Flynn et al, 2018;Moran et al, 2016;Staub et al, 2010;Søndergaard et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…''bulk'' molecular profiling (Flynn et al, 2018;Moran et al, 2016;Staub et al, 2010;Søndergaard et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…One approach to investigate the cellular origins of cancer is to quantify similarities and differences between molecular signatures of tumors and the proposed tissues of origin (Staub et al, 2010). This is based on the hypothesis that the molecular blueprint of normal precursor cells is maintained in developing tumors.…”
Section: Expression Profiling Of Putative Ovarian Cancer Precursor Cellsmentioning
confidence: 99%
“…Tumor samples contain varying amounts of malignant cells, stromal cells and surrounding (contaminating) normal tissue from the biopsy/resection site. The influence of surrounding normal tissue on molecular classification is not clear, although a potential systematic classification bias, caused by normal tissue, has been reported (Elloumi et al., 2011; Staub et al., 2010). Most previously developed diagnostic classifiers require a high tumor content (≥50% tumor) (Meiri et al., 2012; Pillai et al., 2011; Ferracin et al., 2011; Kerr et al., 2012; Rosenfeld et al., 2008; Rosenwald et al., 2010) and use microdissection for tumor cell enrichment, prior to gene expression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The origin of the metastasis needs to be identified as primary treatment regimes for cancer are typically based on the anatomical origin and histological type of the primary tumor. Studies by several groups [4-7,20] have shown that finding the tissue of origin of metastatic samples is possible based on gene expression data. Some of these tests are already commercially available and have been clinically applied [13-15,17].…”
Section: Discussionmentioning
confidence: 99%
“…[20] demonstrated that CUP prediction is possible using available microarray data from about 800 healthy samples and 600 cancer samples extracted from the Gene Expression Omnibus (GEO) [21] as a reference. They were able to construct a predictor using both cancer and healthy tissue samples.…”
Section: Introductionmentioning
confidence: 99%